Plasma Protein Biomarker Candidates for Myelodysplastic Syndrome Subgroups - Majek, Pavel; Pecankova, Klara; Cermak, Jaroslav; Dyr, Jan E (BioMed research international, 2015)
In recent years the plasma proteomes of several different myelodysplastic syndrome (MDS) subgroups have been investigated and compared with those of healthy donors. However, the resulting data do not facilitate a direct and statistical comparison of the changes among the different MDS subgroups that would be useful for the selection and proposal of diagnostic biomarker candidates. The aim of this work was to identify plasma protein biomarker candidates for different MDS subgroups by reanalyzing the proteomic data of four MDS subgroups: refractory cytopenia with multilineage dysplasia (RCMD), refractory anemia or refractory anemia with ringed sideroblasts (RA-RARS), refractory anemia with excess blasts subtype 1 (RAEB-1), and refractory anemia with excess blasts subtype 2 (RAEB-2). Reanalysis of a total of 47 MDS patients revealed biomarker candidates, with alpha-2-HS-glycoprotein and leucine-rich alpha-2-glycoprotein as the most promising candidates.
Keywords: Male; Myelodysplastic Syndromes; alpha-2-HS-Glycoprotein; Adult; ženské pohlaví; Aged; Middle Aged; fetuin A; Biomarkers; biologické markery; lidé středního věku; Humans; Glycoproteins; senioři; Female; glykoproteiny; dospělí; mužské pohlaví; myelodysplastické syndromy; lidé